DEPENDENCE OF THE ACTIVITY OF THE SILKWORM ON THE EXTERNAL ENVIRONMENT (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The characteristics and properties of agricultural plants and animals are manifested under the interaction of hereditary factors and environmental conditions. Each animal or plant requires certain conditions for normal growth, development and the realization of its potential. Environmental factors include food, temperature, humidity, light, air exchange, etc. These factors, individually or in combination, ensure the growth and development of the organism and determine the level of productivity of animals. The sensitivity of the animal organism can be manifested both in normal and adverse environmental conditions.